Scholarly social media profiles and libraries: A review - Ward, Judit; Bejarano, William; Dudás, Anikó (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
This article aims to point out emerging roles and responsibilities for academic librarians with the potential of better integrating the library in the research process. In order to find out how to enhance the online reputation and discoverability of individual faculty members as well as their affiliated institutions, the authors worked side-by-side with researchers in the United States and Europe to explore, create, revise, and disambiguate scholarly profiles in various software applications. In an attempt to understand and organize scholarly social media, including new, alternative metrics, the authors reviewed and classified the major academic profile platforms, highlighting the overlapping elements, benefits, and drawbacks inherent in each. The consensus is that it would be time-consuming to keep one’s profile current and accurate on all of these platforms, given the plethora of underlying problems, also discussed in detail in the article. However, it came as a startling discovery that reluctance to engage with scholarly social media may cause a misrepresentation of a researcher’s academic achievements and may come with unforeseen consequences. The authors claim that current skills and competencies can secure an essential role for academic librarians in the research workflow by means of monitoring and navigating researcher profiles in scholarly social media in order to best represent the scholarship of their host institutions.